2003
DOI: 10.1074/jbc.m300518200
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal Domain of the Measles Virus Nucleoprotein Is Intrinsically Disordered and Folds upon Binding to the C-terminal Moiety of the Phosphoprotein

Abstract: The nucleoprotein of measles virus consists of an Nterminal moiety, N CORE , resistant to proteolysis and a C-terminal moiety, N TAIL , hypersensitive to proteolysis and not visible as a distinct domain by electron microscopy. We report the bacterial expression, purification, and characterization of measles virus N TAIL . Using nuclear magnetic resonance, circular dichroism, gel filtration, dynamic light scattering, and small angle x-ray scattering, we show that N TAIL is not structured in solution. Its sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
339
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 274 publications
(368 citation statements)
references
References 76 publications
26
339
0
3
Order By: Relevance
“…On the other hand, natively unfolded domains are often found in proteins capable of self-assembly into large multimeric complexes such as viral capsids and nucleocapsids (Namba, 2001). Natively unfolded domains both prevent unwanted spontaneous assembly of such proteins, as has been shown for the measles virus nucleoprotein (Longhi et al, 2003), and stabilize multimeric complexes due to folding upon interaction with the correct partners (Namba, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, natively unfolded domains are often found in proteins capable of self-assembly into large multimeric complexes such as viral capsids and nucleocapsids (Namba, 2001). Natively unfolded domains both prevent unwanted spontaneous assembly of such proteins, as has been shown for the measles virus nucleoprotein (Longhi et al, 2003), and stabilize multimeric complexes due to folding upon interaction with the correct partners (Namba, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the C-terminal domain of the nucleoprotein (N tail ) of measles virus, which is involved in a number important functions, is intrinsically unstructured. [22][23][24][25] Metal-thiolate clusters-Several proteins known as metallothioneins rely on metal-thiolate clusters in their functions. There are at least ten known closely related metallothionein proteins expressed in humans.…”
Section: Ligands Interacting With Intrinsically Disordered Proteinsmentioning
confidence: 99%
“…It is monomeric and consists of a flexible linker (aa 474 -517) fused to the X domain (XD) (aa 517-568). This linker is probably conserved also in MV PCT, as suggested by its high protease sensitivity (16).…”
mentioning
confidence: 99%
“…We have recently reported that MV PCT is responsible for the induced folding of N TAIL (16). The induced folding of N TAIL in the presence of its physiological partner opens new perspectives in the structural study of disordered regions within the MV replicative complex.…”
mentioning
confidence: 99%
See 1 more Smart Citation